IMPROVEMENT OF STATE REGULATION OF HIGHER EDUCATIONAL ESTABLISHMENTS ACTIVITIES - Romin A.V. (Pressing Problems of Public Administration, 2015)
In this article analyzes the improvement of state regulation of higher education system activityand the management of higher educational establishments, the problems of quantitative and qualitativeparameters of educational services and their role in improving the economic situation of high school.